The Impact of Industry-University Collaboration on Enhancing Product Attractiveness for Iranian Consumers - Amin Attari; Hossein Ashoori (‫مدیریت بازرگانی)
ObjectiveCollaboration between industry and academia is a significant and intriguing topic within Iran's academic and industrial spheres. A key reason for its importance lies in the potential for industries to leverage the scientific expertise and resources of universities. However, an important question is whether such relations can have a positive impact on the attitude of Iranian consumers, regarding the company's manufactured products. The current research aims to answer this question. Manufacturing companies use different strategies to enhance the appeal of their products from the perspective of end consumers. Using new technology, high-quality raw materials, advertising, appropriate pricing, and appropriate distribution are some of the strategies used by companies to attract consumers. In the meantime, the cooperation between the manufacturing company and the university in the production of the final product has been rarely considered. Considering the high potential for industry-university cooperation, this research investigates whether the cooperation of a manufacturing company with a university influences purchase attractiveness, including product preference, purchase intent, and willingness to pay among Iranian consumers. MethodologyThis research is practical in terms of purpose and experimental in terms of the method of implementation. The statistical population of this research includes Iranian consumers. To examine the cause-and-effect relationship, the impact of a company's collaboration with a university on the attractiveness of its manufactured products was analyzed using an experimental approach. For this purpose, five experimental studies were conducted. FindingsThe findings of this research show that the cooperation of the manufacturing company with a university in product development enhances product attractiveness, resulting in increased product preference, purchase intent, and willingness to pay among Iranian consumers. This impact was confirmed for startups and established companies. Results confirm the mediating role of consumers’ trust in the company's product in the aforementioned relationship. The reason why the products produced in collaboration with the university are more attractive is that such products are more trustworthy in the eyes of Iranian consumers. ConclusionThe findings of this research indicate that Iranian consumers hold a positive perspective on industry-university collaboration in the production of manufactured products. Therefore, manufacturing companies are not only encouraged to collaborate with universities in the development of new products but also to effectively communicate this collaboration to potential consumers. It is suggested that the manufacturing companies emphasize this cooperation in the communication and advertising programs of the products they have produced in collaboration with the university. While this study examined the causal relationship in several scenarios, using an experimental method, further research is recommended to generalize the findings to other contexts, particularly the service sector.